Enhancing Systemic Delivery of Enzymatically Generated RNAi Nanocomplexes for Cancer Therapy. Issue 6 (7th March 2019) - Nam, Hyangsu; Ku, Sook Hee; Yoon, Hong Yeol; Kim, Kwangmeyung; Kwon, Ick Chan; Kim, Sun Hwa; Lee, Jong Bum
Abstract: Despite the superb therapeutic potential of siRNA technology, its clinical application are still limited due to the inherent instability and lack of systemic delivery issues. Recently, the development of long‐chain siRNA has been proposed as a strategy to improve in vivo stability, particularly for efficient physical integration of siRNA molecules into gene carriers. Herein, concatemeric siRNAs are enzymatically synthesized through a rolling circle transcription process, and form stable RNA interference (RNAi) nanocomplexes with a redox‐sensitive glycol chitosan derivative to systemically deliver the concatemeric siRNAs to tumor tissues. The enzymatically generated RNAi nanocomplexes (RNCs) have higher particle stability and less cytotoxicity than the conventional polyelectrolyte complexes. The therapeutic potential of the RNC formulation is verified in vivo as well as in vitro using VEGF as an antiangiogenic target for RNAi‐based anticancer therapy. After systemic administration, RNC is specifically accumulated in tumor tissues and shows a high inhibitory effect on tumor growth. According to the results, the RNC can be considered as a platform technology for efficient tumor‐targeted siRNA delivery systems. Abstract : RNAi nanocomplexes (RNCs) consisting of glycol chitosan and concatemeric siRNA synthesized via rolling circle transcription process are introduced as a potential systemic delivery system for RNAi therapeutics. Remarkable tumor localization properties of RNCs can benefit imaging and therapeutic applications.